„Plan świata” i motywy postępowania bohatera literackiego (I.S. Turgieniew i J. Byron) - Nikołajew, Nikołaj (Studia Rossica Posnaniensia, 2011)
The paper is aimed at understanding peculiarities of behavior of the Russian literary character. The analysis of the early romantic poem Steno by I.S. Turgenev is defined by its imitating of Byron's Manfred. At the same time, the author of the paper indicates items of difference in the “architectonics of actions” as it is viewed by the Russian and English literary character.